Zależna niezależność: Współczesne wyzwania dla ewolucji mediów w Szwajcarii (Politeja, 2023)
DEPENDENT INDEPENDENCE: CONTEMPORARY CHALLENGES FOR MEDIA EVOLUTION IN SWITZERLANDMedia in multicultural and multilingual Switzerland are unique for a number of reasons – including an effectively functioning system of democratic neo-corporationism, favouring a consensual approach and public debate, which in turn requires an effective public information system. The Swiss represent high culture of written word and thus high-quality printed press. Their modern media system, which has taken shape since the federal constitution of 1848, is based on fundamental guarantees for freedom of speech and press, competitive liberal market of private media, journalistic professionalism, a strong role for self- -regulatory bodies and social negotiation. The central public service television plays a key role in the system, acting as an integrative, identity forming and educational medium of social debate. The article discusses in detail the premises for systemic destabilisation and the dilemmas for the further development of the Swiss media system in the 21st century, as a result of the financial crisis of digitalisation and global competition with the internet giants, in the context of rising populism and the social costs of the coronavirus pandemic.